The Effect of Work Culture and Work Motivation on Employee Performance at Manado State University - Kaseger, Megalia Riane; Pangkey, Itje; Dilapanga, Abdul Rahman (Technium Social Sciences Journal, 2021)
This research was conducted to know the influence of work culture and work motivation partially and simultaneously on the performance of employees at Unima. The research uses a quantitative approach. The population is all Unima employees totaling 335 employees spread over six work units. The sampling technique was proportional stratified random sampling with the amount determined by the Slovin rule, and 182 employees were obtained. The data collection technique is a questionnaire that has been tested for validity and reliability. Data analysis is multiple regression analysis through the help of the SPSS program. The results of the study reveal that (1) organizational culture has a positive and significant effect on employee performance at Unima, (2) work motivation has a positive and significant effect on employee performance at Unima, (3) work culture and work motivation simultaneously has a positive and significant effect on performance. Employees at Unima. It is recommended to strengthen work culture, so socialization in order to increase understanding and acceptance of values and norms that have governed attitudes and behavior of working and interacting in the work environment, carried out continuously in line with developments and demands of the organizational environment so that it is strongly internalized. In addition, the organizational climate should be created in a conducive and transparent manner so that employees are free to express their various needs related to their work. The fulfillment of the needs related to his work will encourage him to carry out his duties well.